PSYCHOLOGY IS A KEY ASPECT IN LEARNING FOREIGN LANGUAGES (Scientific journal of the Fergana State University, 2023)
The keys to success in language learning and teaching revolve around understanding the psychology of the students and structuring teaching strategies and activities accordingly. Actually, it is a clear and undeniable problem in contemporary techniques of teaching languages that personality variables play a part in language learning. The subject on which this article concentrates has grown to be essential to education.